2000
DOI: 10.1016/s0014-5793(00)01525-8
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of organic cation transporter OCT2 expression in rat kidney

Abstract: Rat (r) OCT2 was identified as the second member of the organic cation transporter (OCT) family, and is predominantly expressed in the kidney. We reported previously that rOCT2 was responsible for the gender differences in renal basolateral membrane organic cation transport activity. As renal rOCT2 expression in males is much higher than that in females, we hypothesized that rOCT2 expression may be under the control of sex hormones. Treatment of male and female rats with testosterone significantly increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 26 publications
4
101
2
1
Order By: Relevance
“…Considering the results in the experiment 2 that there was no difference in blood L-FABP, Cys-C, β2-MG, and glucose levels between the sham-operated and orchidectomized male rats, it was indicated testosterone was involved in the reabsorption process. In the kidney, there are receptors and transporters such as sodium/glucose co-transporter-2 and organic cation transporter 2, which have been reported that testosterone changed their expression levels in rats (Pávó et al, 1995;Urakami et al, 2000;Ljubojevic et al, 2004;Sabolic et al, 2012;Loh et al, 2017). Meanwhile, sex differences of megalin and cubilin, receptors related to reabsorption of LMWPs and albumin which are localized in the renal proximal tubules (Cui et al, 1996;Orlando et al, 1998;Birn et al, 2000;Oyama et al, 2005;Hvidberg et al, 2005;Kaseda et al, 2007;Amsellem et al, 2010), have been ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the results in the experiment 2 that there was no difference in blood L-FABP, Cys-C, β2-MG, and glucose levels between the sham-operated and orchidectomized male rats, it was indicated testosterone was involved in the reabsorption process. In the kidney, there are receptors and transporters such as sodium/glucose co-transporter-2 and organic cation transporter 2, which have been reported that testosterone changed their expression levels in rats (Pávó et al, 1995;Urakami et al, 2000;Ljubojevic et al, 2004;Sabolic et al, 2012;Loh et al, 2017). Meanwhile, sex differences of megalin and cubilin, receptors related to reabsorption of LMWPs and albumin which are localized in the renal proximal tubules (Cui et al, 1996;Orlando et al, 1998;Birn et al, 2000;Oyama et al, 2005;Hvidberg et al, 2005;Kaseda et al, 2007;Amsellem et al, 2010), have been ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the expression of rOCT2 was decreased in rats with chronic renal failure (Ji et al, 2002), hyperuricemia (Habu et al, 2003), and diabetes mellitus (Thomas et al, 2004). Urakami et al (2000) reported that the expression of rOCT2 was up-regulated by testosterone and down-regulated by estradiol in rats. It was also suggested that the lowered plasma level of testosterone was responsible for the decreased rOCT2 expression (Ji et al, 2002).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Therefore, the gender differences in lactate levels are more likely related to the fundamental difference in sex hormone levels in males and females. Urakami demonstrated in rats that OCT2 is responsible for the gender differences in renal basolateral membrane OCT activity, and OCT2, but not OCT1, is sexually up-regulated by testosterone and down-regulated by estradiol in the kidney [8][9][10] . In our clinical study of 1021 patients with T2DM, we observed that blood lactate levels were due to gender differences, with females having significantly higher blood lactate levels than males treated with metformin (unpublished data).…”
Section: Metformin (N=200)mentioning
confidence: 99%
“…A kinetic analysis of metformin transport and its distribution in rats suggested that metformin is a superior substrate for renal OCT2 rather than hepatic OCT1, and renal OCT2 plays a dominant role in metformin pharmacokinetics [4] . In addition, OCT2 is responsible for the observed gender differences in SLC22A2 gene 808 G/T variant is related to plasma lactate concentration in Chinese type 2 diabetics treated with metformin www.chinaphar.com Li Q et al Acta Pharmacologica Sinica npg renal basolateral membrane organic cation transporting activity [7][8][9] ; however, to date no studies related to human OCT2 and its relevance to metformin-treatment in diabetic populations have been reported.…”
Section: Introductionmentioning
confidence: 99%